Should corporations be socially responsible and green? - DesJardins, Joe (Henry Stewart Talks, 2011)
Models of corporate social responsibility, Economic model and responsibility to shareholders, Corporate philanthropy, Corporations as citizens, Stakeholder model, Social entrepreneurship, Sustainability, The "Business Case" for sustainability
Reviewed at 2019/01/31